Growth and yield of different oat (Avena sativa) varieties in Lalitpur district of Nepal - Pant, Shankar Raj; Ghimire, Ram Prasad; KC, Prenil; Upreti, Sujaya (Journal of Agriculture and Natural Resources, 2022)
Oat (Avena sativa) is considered as one of the best fodders to mitigate the present seasonal feed deficit for ruminants in Nepal. The study was undertaken to evaluate eleven oat varieties for fodder and seed yield at the Khumaltar condition from December 2021 to April 2022. The experiment was laid out in Randomized Complete Block Design (RCBD) with three replications. The fodder oat varieties; Ever leaf, Titan, Baler no. 1, Sweet oat, Monida, Qingyin no. 1, Qinghai no. 444, Kona, Swan Pak, Longford, and Netra (as a check variety) were used as the treatments. An experimental unit was a 4 m × 3 m sized plot with the row to row spacing of 0.30 m and continuous sowing within a row. A total of two cuttings were taken for fodder. The observations on growth and yielding characters comprising of plant height, leaf area, number of tillers plant-1, number of leaves/tiller, fodder dry matter, seed and straw yield were recorded. The results showed the fodder dry matter yields ranged from 2.35 to 3.58 t/ha and were not significantly different (p>0.05) among the varieties. The seed and straw yields were obtained statistically different (p<0.05) among the varieties. Netra (2.90 t/ha) and Kona (2.88 t/ha) produced higher seed yields. Similarly, the highest straw yield was produced for the variety Longford (8.73 t/ha).